2006
DOI: 10.1074/jbc.m603646200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Satin Hair Mutant Gene Foxq1 Is among Multiple and Functionally Diverse Regulatory Targets for Hoxc13 during Hair Follicle Differentiation

Abstract: It is increasingly evident that the molecular mechanisms underlying hair follicle differentiation and cycling recapitulate principles of embryonic patterning and organ regeneration. Here we used Hoxc13-overexpressing transgenic mice (also known as GC13 mice), known to develop severe hair growth defects and alopecia, as a tool for defining pathways of hair follicle differentiation. Gene array analysis performed with RNA from postnatal skin revealed differential expression of distinct subsets of genes specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 58 publications
3
80
0
2
Order By: Relevance
“…This might indicate that the cuticle and cortex cells are derived from common precursors and further that Sox21 might be involved in a lineage restriction mechanism. Recently, it has been shown that Hoxc13 is expressed in the precursors of all 3 hair shaft-forming compartments (cuticle, cortex, and medulla) and mainly regulates the expression of medulla-specific genes by directly regulating Foxq1 expression (18). However, the expression of both Hoxc13 and Foxq1 was found unaltered in the Sox21-null mouse, indicating that Sox21 functions downstream or in parallel with the Hoxc13 cascade in the hair follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might indicate that the cuticle and cortex cells are derived from common precursors and further that Sox21 might be involved in a lineage restriction mechanism. Recently, it has been shown that Hoxc13 is expressed in the precursors of all 3 hair shaft-forming compartments (cuticle, cortex, and medulla) and mainly regulates the expression of medulla-specific genes by directly regulating Foxq1 expression (18). However, the expression of both Hoxc13 and Foxq1 was found unaltered in the Sox21-null mouse, indicating that Sox21 functions downstream or in parallel with the Hoxc13 cascade in the hair follicle.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Among these, we identified keratin and its related genes, Krt32, Krt82, Krtap5-1, Krtap5-4, and Krtap12-1, which are known to be expressed only in the Cuh (9,10,17,18) and validated their down-regulation in Sox21 ÏȘ/ÏȘ skin by quantitative PCR (Q-PCR) (Fig. 4B).…”
Section: Sox21 Is a Master Regulator Of Keratin Gene Network In The Cuhmentioning
confidence: 93%
“…Defects in Hox C13 expression have been shown to give rise to loss of hair in mutant mice. Potter et al (2006) also showed that the regulatory transcription factor-encoding gene Foxq, is a downstream target for Hox C13 and acting through a common regulatory pathway controls differentiation of hair follicle medulla. Other transcriptional regulatory molecules include (a) the Sox 9 gene product, which has been ascribed an essential role in development of ORS and stem cell compartment of murine hair follicles in which it has continuous expression (Vidal et al, 2005), (b) Foxe 1, detected in the lower undifferentiated region of the HF and involved in hair follicle morphogenesis, as an apparent downstream target of the Shh/ Gli pathway (Brancaccio et al, 2004) and (c) Gata 3 (Kaufman et al, 2003) which has been ascribed a role in early specification of basal cells towards IRS as opposed to hair shaft lineage.…”
Section: General Properties Of Integumental Tissuesmentioning
confidence: 97%
“…An essential role for the transcriptional repressor Cutl 1 has been indicated in the development of IRS (Ellis et al, 2001). Similarly, the Hox family of transcription factors, which are usually expressed sequentially according to spatial position and time with respect to their positions in the Hox complex has been ascribed a role in regulation of patterning and developmental morphology of hair follicles (and other tissues of the integument) (Potter et al, 2006). Expression of Hox C13 was detected in medulla, cortex, IRS, companion layer and upper inner ORS.…”
Section: General Properties Of Integumental Tissuesmentioning
confidence: 99%
“…In mouse Foxq1 has been reported to be regulated by Hoxa1 (Martinez-Ceballos et al, 2005), Hoxc13 (Potter et al, 2006) and TgfÎČ (Zhang et al, 2011). In human FOXQ1 has been shown to be a target of the Wnt pathway Xia et al, 2014).…”
Section: Transcriptionmentioning
confidence: 99%